1980
DOI: 10.7326/0003-4819-93-6-875
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blocking Agents in the Treatment of Cardiovascular Disorders. Part I: Basic and Clinical Electrophysiologic Effects

Abstract: Calcium ions play an important role in the cardiovascular system. They are involved in electrophysiologic processes, link excitation to muscular contraction, control energy storage and utilization, and constrict vascular smooth muscle in coronary and systemic arteries. A new group of pharmacologic agents that block the passage of calcium ions across cell membranes has been developed. These agents act during the slow inward current of cellular depolarization. The most extensive clinical experience has been obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(47 citation statements)
references
References 100 publications
0
47
0
Order By: Relevance
“…By comparison, little is known about the Ca channel (Hagiwara & Byerly, 1981;McDonald, 1982), and it will be interesting to see whether further studies with Ca channel blockers narrow this gap. On the clinical side, Ca channel blocking agents have become increasingly important in the treatment of cardiac and vascular disorders (Antman, Stone, Muller & Braunwald, 1980). It is almost certain that membrane potential and the frequency of Ca channel opening are key elements in the pharmacology of these drugs.…”
Section: Conclu8ionsmentioning
confidence: 99%
“…By comparison, little is known about the Ca channel (Hagiwara & Byerly, 1981;McDonald, 1982), and it will be interesting to see whether further studies with Ca channel blockers narrow this gap. On the clinical side, Ca channel blocking agents have become increasingly important in the treatment of cardiac and vascular disorders (Antman, Stone, Muller & Braunwald, 1980). It is almost certain that membrane potential and the frequency of Ca channel opening are key elements in the pharmacology of these drugs.…”
Section: Conclu8ionsmentioning
confidence: 99%
“…Other studies have demonstrated that rapid depolarizations result in increased cytosolic Ca 2þ concentration (calcium overload) and ERP shortening in cardiac myocytes 4,[16][17][18][19] via changes in I CaL , I To and I Na and that inhibition of I Na results in decreased conduction velocity. Further, Balana et al reported that chronic AF was associated with down-regulated IK ATP currents, 8) and Brundel et al reported that mRNA levels of Kir6.2, which encodes for a portion of the IK ATP protein, are reduced in patients with 7) They also demonstrated that the reduction in levels of Kv4.3, Kv1.5 and Kv3.1, which encode for portions of the I To , IK ur and IK Ach proteins, could be reversed by maintenance of sinus rhythm.…”
Section: Atrial Refractorinessmentioning
confidence: 99%
“…Until the results of this trial become available and are widely disseminated to the practicing physician, it will be difficult to credit beta-blocking drugs with a major role in the decline in cardiovascular mortality. Similarly, while the new calcium channel antagonists, verapamil and nifedipine, appear to hold great promise for the treatment of coronary vasospasm and myocardial ischemia 24 in the United States, they have not yet been approved by the Federal Drug Administration (FDA). They remain investigational and are not readily available for physician use.…”
Section: New Drugs Surgical and Diagnostic Techniquesmentioning
confidence: 99%